Strategy Of Successful Sake Business Reflected In Joyce Lebra's The Scent Of Sake Novel (2009): An Individual Psychological Perspective - Fitri, Khoirina Nur; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This research paper is aimed to show the survival strategy of successful sake business of Joyce Lebra's novel which is analyzed by using individual psychological. The objectives of the research are to analyze the novel based on individual psychological proposed by Alfred Adler. This research paper belongs to qualitative research. Data of the research are divided into two, primary and secondary data. The primary data of the research is The Scent of Sake novel and secondary data of the research are website, books and other sources about individual psychological that support the analysis. The method to analyze of this data is descriptive analysis. The researcher comes to the conclusion as follows. Based on the individual psychological analysis, Joyce Lebra illustrates individual psychological phenomena in which an individual has desire and works hard in achieving a goal. The author portrays persistence and struggle of Rie-Omura in advancing her family sake business. She uses her creativity and opportunity in managing business strategy. Striving for superiority is needed by Rie to overcome her inferiority feeling and achieve her final goal.